Impact of Propofol Bolus Administration on the Nociceptive Flexion Reflex Threshold and Bispectral Index in Children-A Case Series - Maximilian David Mauritz; Felix Uhlenberg; Eik Vettorazzi; Chinedu Ulrich Ebenebe; Dominique Singer; Philipp Deindl (MDPI AG, 2021)
We analyzed the impact of propofol administration during continuous sedation and analgesia on the nociceptive flexion reflex threshold (NFRT) and Bispectral Index (BIS) in ventilated children. We examined patients who received propofol before planned endotracheal suctioning. Patients were clinically assessed using the modified Face, Legs, Activity, Cry, Consolability (mFLACC) scale and COMFORT-B (Comfort Behavior) scale. We continuously recorded the NFRT and BIS. We recorded 23 propofol administrations in eight patients with an average age of 8.6 ± 3.5 years. The median (minimum-maximum) scores for the mFLACC scale and COMFORT-B scale were 0 (0-5) and 6 (6-17), respectively, before the bolus. The administration of a weight-adjusted propofol bolus of 1.03 ± 0.31 mg/kg resulted in an increase in NFRT and burst-suppression ratio; BIS and electromyogram values decreased. Changes from baseline (95% CI) after propofol bolus administration were BIS −23.9 (−30.8 to −17.1), EMG -10.5 dB (−13.3 to −7.7), SR 14.8 % (5.6 to 24.0) and NFRT 13.6 mA (5.5 to 21.7). Further studies are needed to determine whether sedated children may benefit from objective pain and sedation monitoring with BIS and NFRT.